Diminutif dalam Bahasa Belanda: Tinjauan dari Sudut Pandang Makna - Aziz, Abdul (CV. Pena Persada, 2019)
The study aims at describing diminutive lexemic senses in Dutch. The data that will be analyzed are any Dutch words or lexemes ended in –je suffix with its many realizations. The theory used is denotative, connotative and conversive meaning. The method used is qualitative-descriptive one. The study reveals the results as below; firstly, Dutch diminutive lexemes if seen from its sense and meaning express the idea of ‘littleness/smallness’ in quality or in quantity. This kind of sense/meaning would be best called as denotative meaning; secondly, denotative meaning of diminutive lexemes can change to its connotative meaning if there is subjective influence in which the community plays an important role; Thirdly, there are some Dutch diminutive lexemes which have different meaning from its subjective and objective sense (denotative and connotative). It is also to be called as conversive diminutive in which the meaning changes radically from its primary one.